Platelet Activation and Platelet-erythrocyte Aggregates in End-stage Renal Disease Patients on Hemodialysis - Sirolli, Vittorio; Strizzi, Luigi; Di Stante, Silvio; Robuffo, Iole; Procopio, Antonio; Bonomini, Mario (Thrombosis and Haemostasis, 2001)
Activated platelets may engage in dynamic interplay with other blood cells. We examined the evidence for platelet activation and the formation of platelet-erythrocyte aggregates in chronic hemodialysis patients. Circulating activated platelets (P-selectin/CD63-positive platelets) were higher than normal controls (p <0.001) and further increased during hemodialysis sessions, the increase being higher when patients were dialyzed with cellulosic than with synthetic membranes. We found direct evidence of uremic platelet-erythrocyte adherence in vitro and increased levels of circulating platelet-erythrocyte aggregates in dialysis patients, which represents a new observation in uremia. Platelet-erythrocyte aggregates were subject to further increase during hemodialysis, and again higher levels were found with cellulosic than synthetic membranes. This phenomenon was reproduced in vitro by both ADP and PAF, but not by either complement factor C3a or by heparin concentrations corresponding to those used for clinical hemodialysis. We conclude that platelet-erythrocyte aggregates occur in hemodialysis patients probably owing to a primary platelet activation mechanism.
Keywords: Platelet; erythrocyte; platelet-erythrocyte interaction; flow cytometry; hemodialysis